IMPLEMENTASI PERATURAN DAERAH NOMOR 12 TAHUN 2010 TENTANG RETRIBUSI PELYANAN PARKIR DI RUMAH SAKIT ARIFIN NU’MAN KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Fatmawati Fatmawati (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract This Research Tried 1). To find out communication, resources, disposition and bureaucratic structure in influencing the Implementation of Regional Regulation Number 12 of 2010 concerning Parking Service Retribution at Arifin Nu'mang Hospital, Panca Rijang District, Sidenreng Rappang District 2). To find out how parking services at Arifin Nu'mang Hospital, Panca Rijang District, Sidenreng Rappang Regency. The population in this study was 1600 parking service users. The sampling technique used is the probability of sampling which uses more random samples. The sample used was 94 respondents with quantitative descriptive research types. Data collection techniques used in this study were observation, interviews, questionnaires and literature studies. The collected data is then analyzed using data analysis techniques using frequency tables and likert scales. Based on the results of the study, the factors that influence the Implementation of Regional Regulations are communication with a percentage of 58%, resources with a percentage of 60%, disposition with 56%, and bureaucratic structure with a percentage of 64%, so that an average of 59% is included not good